Dampak Media Sosial bagi Remaja - Fany Mulyono (Jurnal Simki Economic, 2021)
Technology is currently developing very rapidly, especially the internet which is known as a social network. Such as eliminating distance, space and time and also being able to connect with anyone and anytime. Social media also brings many impacts, both positive and negative. Social media users are mostly teenagers and children who still need supervision, therefore the big impact is on them. Social media has positive impacts and benefits in the development of science and technology, for example making it easier to communicate, finding and accessing information, developing relationships, adding friends and so on, but on the other hand social media also has a negative impact on children and society. Teenagers like the change in attitude shown after they are addicted to social networks as they become lazy because they are too busy with their social networks, they also forget their obligations as students.